Aorta Measurements are Heritable and Influenced by Bicuspid Aortic Valve - Martin, Lisa J.; Hinton, Robert B.; Zhang, Xue; Cripe, Linda H.; Benson, D W. (Frontiers in Genetics, 2011)
Abstract: Word Count 266, 1609 characters Objectives: To determine whether the contributions of genetics and bicuspid aortic valve (BAV) independently influence aortic (Ao) dimensions. Background: Ao dilation is a risk factor for aneurysm, dissection, and sudden cardiac death. Frequent association of BAV with Ao dilation implicates a common underlying defect possibly due to genetic factors. Methods: Families enriched for BAV underwent standardized transthoracic echocardiography. In addition to BAV status, echocardiographic measures of Ao (annulus to descending Ao), pulmonary artery and mitral valve annulus diameters were obtained. Using variance components analysis, heritability was estimated with and without BAV status. Additionally, bivariate genetic analyses between Ao dimensions and BAV were performed. Results: Our cohort was obtained from 209 families enriched for BAV. After adjusting for age, body surface area and sex, individuals with BAV had a statistically significant increase in all echocardiographic measurements (p < 0.006) except descending Ao and mitral valve annulus. Individuals with BAV were at greater odds of having Ao dilation (OR = 4.44, 95% CI 2.93 – 6.72) than family members without BAV. All echocardiographic measurements exhibited moderate to strong heritability (0.25 to 0.53), and these estimates were not influenced by inclusion of BAV as a covariate. Bivariate genetic analyses supported that the genetic correlation between BAV and echo measures were not significantly different from zero. Conclusions: We show for the first time that echocardiographic measurements of Ao, pulmonary artery and mitral valve annulus diameters are quantitative traits that exhibit significant heritability. In addition, our results suggest the presence of BAV independently influences the proximal Ao and pulmonary artery measures but not those in the descending Ao or mitral valve annulus.